Rapid Estimation of Gustatory Sensitivity Thresholds with SIAM and QUEST - Höchenberger, Richard; Ohla, Kathrin (Frontiers in Psychology, 2017)
Adaptive algorithms for sensitivity estimation are typically developed for and applied to the non-chemical senses. In this manuscript, we present data from two adaptive methods (QUEST and SIAM), modified to rapidly estimate taste thresholds for four basic taste qualities in a yes-no-task. We show that a) gustatory thresholds can be obtained in a time efficient manner (within only 3-7 minutes using QUEST and 6-10 minutes using SIAM), b) both methods yield good test-retest correlations, with higher test-retest correlations for QUEST c) QUEST and SIAM thresholds were highly correlated ($r=0.88$) Together, the findings suggest that QUEST and SIAM are suitable for the quick and reliable measurement of gustatory sensitivity. Moreover, the high correlation between methods indicates that the QUEST procedure measures similar perceptual properties as the bias-free SIAM. These methods allow reliable taste threshold estimations with low strain on participants redndering them particularly advantageous for threshold estimation in participants with limited attentional or mnemonic capacities and for time-constrained application such as clinical populations and children.